Economic Risks Associated with Bit Coin: A Comprehensive Analysis - Shurooq Abbas Merza (HM Journals, 2023)
Bitcoin, the pioneering cryptocurrency, has revolutionized the financial landscape, but its use is not without economic risks. This paper provides a comprehensive analysis of the economic risks stemming from the use of Bitcoin. It explores the volatility of Bitcoin and the factors contributing to its price instability, including regulatory uncertainty, cybersecurity threats, and market manipulation. Additionally, it delves into the implications of illicit activities and money laundering associated with Bitcoin, highlighting the need for robust regulatory frameworks to mitigate these risks. The paper also examines the environmental impact of Bitcoin mining, emphasizing its energy-intensive nature and carbon footprint. The systemic risks posed by Bitcoin, such as market volatility spillover, interconnectedness with traditional financial institutions, counterparty risks, lack of regulation, financial crime, and cybersecurity vulnerabilities, are thoroughly analyzed. Through a comprehensive review of the literature and an in-depth understanding of the subject matter, this paper provides insights into the multifaceted economic risks associated with Bitcoin. It underscores the importance of proactive measures to address these risks, including enhanced regulations, transparency, cybersecurity measures, and sustainability practices. By mitigating these risks, the paper argues that Bitcoin can play a more secure and sustainable role in the future of finance.